Modes of Antarctic tidal grounding line migration revealed by Ice, Cloud, and land Elevation Satellite-2 (ICESat-2) laser altimetry - B. I. D. Freer; B. I. D. Freer; O. J. Marsh; A. E. Hogg; H. A. Fricker; L. Padman (The Cryosphere, 2023)
Tide-forced short-term migration of the grounding line (GL) of Antarctic ice shelves can impact ice dynamics at the ice sheet margins and obscures assessments of long-term GL advance or retreat. However, the magnitude of tidally induced GL migration is poorly known, and the spatial patterns and modes of variability are not well characterised. Here we develop and apply a technique that uses Ice, Cloud, and land Elevation Satellite-2 (ICESat-2) repeat-track laser altimetry to locate the inland limit of tidal ice shelf flexure for each sampled tide, enabling the magnitude and temporal variability of tidal GL migration to be resolved. We demonstrate its application at an ice plain north of Bungenstockrücken, in a region of the southern Ronne Ice Shelf subject to large ocean tides. We observe a 1300 km2 area of ephemeral grounding over which the GL migrates by up to 15 km between low and high tide and identify four distinct modes of migration: linear, asymmetric, threshold and hysteresis. The short-term movement of the GL dominates any long-term migration signal in this location, and the distribution of GL positions and modes contains information about spatial variability in the ice–bed interface. We discuss the impact of extreme tidal GL migration on ice shelf–ocean–subglacial systems in Antarctica and make recommendations for how GLs should be more precisely defined and documented in future by the community.